Analisis Tekanan Pori dan Mekanisme Pembentukan Overpressure Menggunakan Data Open Hole Log Sub Cekungan Jambi, Cekungan Sumatra Selatan - Hari Wiki Utama; Bagas Adith Setyo Wicaksono; Bagus Adhitya (BBPMGB LEMIGAS, 2025)
Field X is one of the oil and gas production fields in the Jambi Sub-Basin. This study analyzes subsurface pore pressure using drilling and logging data. Subsurface zones generally have normal and abnormal zones. Abnormal zones are also called overpressure. Determining overpressure is important in the field of drilling hazards such as determining the weight of drilling mud. Determining overpressure is done to anticipate loss or kick. Accurate and appropriate analysis in determining overpressure makes well drilling operations in the oil and gas industry more efficient, safe and effective. In this study, there are three wells in field X with values of pore pressure of the BGS-1 well ranging from 338.6-3541 psi measured from 238 m SSTVD to a depth of 2489.91 m SSTVD. The value of the pore pressure of the BGS-2 well ranges from 403.8-3459 psi measured from 283.9 m to a depth of 1921 m SSTVD and the value of the pore pressure of the BGS-8 well ranges from 853-3455 psi measured from 600 m to a depth of 1783 m SSTVD. The overpressure mechanism in Field X occurs due to the loading mechanism or disequilibrium compaction. This is in accordance with the geological conditions of the Gumai formation which is in the transgression phase dominated by clay lithology causing an increase in pore pressure due to the inability of fluids to exit the rock during compaction.